Serum Vitamin D Levels and Risk of Liver Cancer: A Systematic Review and Dose-Response Meta-Analysis of Cohort Studies - Zhang, Yonggui; Jiang, Xuefeng; Li, Xiangjun; Găman, Mihnea-Alexandru; Kord-Varkaneh, Hamed; Rahmani, Jamal; Salehi-Sahlabadi, Ammar; Day, Andrew S; Xu, Yan (Nutrition and cancer, 2021)
Data regarding the relationship between serum vitamin D levels and the risk of liver cancer are conflicting. Therefore, we performed a systematic review and dose-response meta-analysis of all available data of cohort studies on the association of 25-OH-vitamin-D levels with the risk of hepatocellular carcinoma. We conducted a systematic search in PubMed-MEDLINE, Scopus, Cochrane and Web of Science databases for prospective observational studies conducted on the general population from inception to May 2019. Six studies provided data from 6357 participants. According to the pooled HR, the subjects with the highest serum concentrations of vitamin D had a 47% lower risk of liver cancer vs. the subjects with the lowest serum concentrations of vitamin D (pooled HR: 0.53, 95% CI: 0.41-0.68; P < 0.001). There was no significant heterogeneity among the studies (P = 0.431, I 2 = 0.0). The pooled HR from the random-effects dose-response model indicated an indirect significant linear association between vitamin D and the risk of liver cancer (coef = −0.017, P < 0.001). However, there was no significant nonlinear dose-response association between serum vitamin D and the risk of liver cancer (coef = −0.0001, P = 0.342). The evidence from this meta-analysis suggests that there may be an inverse relationship between serum vitamin D levels and the risk of liver cancer.